Palliative Care in Pediatric Oncology (Pediatric Oncology,, 2018)
This textbook is the first to focus on comprehensive interdisciplinary care approaches aimed at enhancing the wellbeing of children with cancer and their families throughout the illness experience. Among the topics addressed are the epidemiology of pediatric cancer distress, including physical, emotional, social, and spiritual dimensions; the role of the interdisciplinary team; communication and advance care planning; symptom prevention and management; care at the end of life; family bereavement care; and approaches to ease clinician distress. The contributing authors are true experts and provide guidance based on the highest available level of evidence in the field. The book has not only an interdisciplinary but also an international perspective; it will appeal globally to all clinicians caring for children with cancer, including physicians, nurses, psychosocial clinicians, and chaplains, among others.